2016
DOI: 10.1177/1088868316656701
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Review of Social Identification and Health in Organizational Contexts

Abstract: We provide a meta-analytical review examining two decades of work on the relationship between individuals' social identifications and health in organizations (102 effect sizes, k = 58, N = 19,799). Results reveal a mean-weighted positive association between organizational identification and health ( r = .21, T = .14). Analysis identified a positive relationship for both workgroup ( r = .21) and organizational identification ( r = .21), and in studies using longitudinal/experimental ( r = .13) and cross-section… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
179
5
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 218 publications
(204 citation statements)
references
References 225 publications
(289 reference statements)
17
179
5
3
Order By: Relevance
“…By contrast, there is now a wealth of evidence that multiple group memberships, and the social identities arising from them, are protective in a wide range of contexts, and for both vulnerable and less vulnerable populations (Crabtree, Haslam, Postmes & Haslam, 2010;Gleibs, Haslam, Haslam & Jones, 2011;Khan et al, 2014;Sani et al, 2015, Steffens, Haslam, Schuh, Jetten & van Dick, 2016. Instead, we can infer from the social identity model that there are two reasons why our studies, along with previous research, have found limited evidence for the stress buffering hypothesis -both relating to the measurement of social support.…”
Section: Discussioncontrasting
confidence: 78%
“…By contrast, there is now a wealth of evidence that multiple group memberships, and the social identities arising from them, are protective in a wide range of contexts, and for both vulnerable and less vulnerable populations (Crabtree, Haslam, Postmes & Haslam, 2010;Gleibs, Haslam, Haslam & Jones, 2011;Khan et al, 2014;Sani et al, 2015, Steffens, Haslam, Schuh, Jetten & van Dick, 2016. Instead, we can infer from the social identity model that there are two reasons why our studies, along with previous research, have found limited evidence for the stress buffering hypothesis -both relating to the measurement of social support.…”
Section: Discussioncontrasting
confidence: 78%
“…In every case, higher social identification was associated with lower levels of depression and fewer depressive symptoms (mean r = −.25). Likewise, Steffens, Haslam, Schuh, Jetten, and van Dick () examined the relationship between social identification and health in organisational settings (based on 58 independent samples and close to 20 000 participants) and found that higher workgroup identification and higher organisational identification were reliably associated with better health (in each case, r = .21). Furthermore, the social identification–health relationship for indicators of both psychological and physical health were positive ( r = .23 and r = .16, respectively).…”
Section: A Social Identity Analysis Of Health and Well‐beingmentioning
confidence: 99%
“…Instead, people can experience being part of numerous groups, including their family, friends, colleagues, or study peers. These processes lead to positive outcomes, such as improved well‐being or less strain (Mael & Ashforth, ; van Dick et al ., ; see also Steffens, Haslam, Schuh, Jetten, & van Dick, for a meta‐analysis of over 60 studies). Due to these positive effects, social identification has been coined the social cure (Haslam, Jetten, Cruwys, Dingle, & Haslam, ).…”
Section: Introductionmentioning
confidence: 99%